2016
DOI: 10.1039/c6ta05207j
|View full text |Cite
|
Sign up to set email alerts
|

Degradable cellulose acetate/poly-l-lactic acid/halloysite nanotube composite nanofiber membranes with outstanding performance for gel polymer electrolytes

Abstract: The biodegraded cellulose acetate (CA)/poly-l-lactic acid (PLLA)/halloysite nanotube composite nanofiber membranes were fabricated for the preparation of gel polymer electrolytes (GPEs) used in lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…The outer and inner hydrosilicates surfaces saturated with OH‐groups can be modified by various organic compounds as well as be decorated by metallic or oxide phases ,. High aspect ratio affects on particles aggregation: entangling of nanotubes and nanoscrolls is used for production of self‐supported and composite membranes ,. Individual nanoscrolls demonstrate good mechanical properties,, which are appropriate for reinforcement of polymer composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outer and inner hydrosilicates surfaces saturated with OH‐groups can be modified by various organic compounds as well as be decorated by metallic or oxide phases ,. High aspect ratio affects on particles aggregation: entangling of nanotubes and nanoscrolls is used for production of self‐supported and composite membranes ,. Individual nanoscrolls demonstrate good mechanical properties,, which are appropriate for reinforcement of polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] High aspect ratio affects on particles aggregation: entangling of nanotubes and nanoscrolls is used for production of self-supported and composite membranes. [20,21] Individual nanoscrolls demonstrate good mechanical properties, [22,23] which are appropriate for reinforcement of polymer composites. Change of Mg by a delement like Ni enhances magnetic properties of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the insolubility in organic solvents, natural polymers are generally difficult to use directly as gel polymer skeletons to reserve organic liquid electrolytes in conventional Li batteries. Modification strategies through grafting or combining with other macromolecules have also been demonstrated . For instance, by combining starch with γ‐(2,3‐epoxypropoxy)propyltrimethoxysilane, organic electrolyte can be gelled via the chemical substitution reaction between ─OH groups and ─Si─(OCH 3 ) 3 (Figure A,B) .…”
Section: Natural Primordial Biological Polymersmentioning
confidence: 99%
“…Modification strategies through grafting or combining with other macromolecules have also been demonstrated. 51,[57][58][59][60][61][62][63] For instance, by combining starch with γ-(2,3-epoxypropoxy)propyltrimethoxysilane, organic electrolyte can be gelled via the chemical substitution reaction between ─OH groups and ─Si─(OCH 3 ) 3 (Figure 2A,B). 57 Recently, Dong et al reported a new kind of bio-based poly (methyl vinyl ether-alt-maleic anhydride) composite electrolyte layer supported by natural bacterial cellulose and demonstrated its effectiveness in Li metal anode protection.…”
Section: Gel Polymer Electrolyte or Separatormentioning
confidence: 99%
“…Nevertheless, its inherent brittleness, poor heat resistance, poor barrier properties, and slow crystallization rate largely restrict its application in LMBs. Thus, a proper polymer blend system comprising cellulosic materials and PLLA would enable good thermal properties and promote the transmission of Li ions …”
Section: Introductionmentioning
confidence: 99%